Proposals for the enhanced CARTIS - Pollard, Maureen A. (CEDP St. MichaelBB, 1992)
It is envisaged that CARTIS will operate within the framework of the Caribbean Trade Centre. On-line access to the CARTIS databases will be accomodated through the use of the Information Centre at Barbados's External Telecommunications Limited. Medium-term objectives have been identified. A pilot project is currently being executed to test and refine the principal logistical and operational features of the enhanced CARTIS. Improvements in the management system, management accounting and standards for the information systems were identified as issues to be addressed by the enhanced CARTIS.